Comentarios y análisis sobre el proceso constituyente en Chile - Zegarra Llanos, Irene Jetsabel (Pontificia Universidad Católica del Perú, 2022)
With the social outbreak in Chile in October 2019, a series of demonstrations and citizen mobilizations of different sectors of society began, which promoted various requests for social claims and demands. It is from this event that, on November 12 of that year, a presidential speech was issued, through which three major agreements were proposed to overcome the crisis that was being experienced, and one of those agreements was the agreement for a new constitution.This promise gave rise to the formation of the Constitutional Convention, the body which, after a long and arduous period of work, has recently presented a new draft constitutional text, which will be accepted or rejected by means of a plebiscite to be held in September of this year. In this context, the purpose of the interview is to analyze and evaluate the most decisive aspects of the constitutional process.

Con el estallido social en Chile ocurrido en octubre del 2019, se inició un conjunto de manifestaciones y movilizaciones ciudadanas de distintos sectores de la sociedad que impulsaron diversas solicitudes de reivindicaciones y demandas sociales. Es a partir de este suceso que, el 12 de noviembre del mencionado año, se emitió un discurso presidencial, a través del cual se plantearon tres grandes acuerdos para superar la crisis que se vivía, y, uno de esos acuerdos, fue el acuerdo por una nueva constitución.Dicha promesa dio origen a la conformación de la Convención Constitucional, el órgano que, luego de un periodo de trabajo bastante arduo y largo, recientemente ha presentado un nuevo proyecto de texto constitucional, el cual será aceptado o rechazado mediante un plebiscito a celebrarse en septiembre del presente año. En este contexto, la entrevista tiene la finalidad de analizar y evaluar los aspectos más determinantes sobre el suscitado proceso constituyente.
Comments and analysis on the constituent process in Chile
Keywords: Constitution; Constituent process; Constitutional Convention; Democratic State; Constitución; Proceso constituyente; Convención constitucional; Estado democrático; https://purl.org/pe-repo/ocde/ford#5.05.00